Generation sleepless : why tweens and teens aren't sleeping enough and how we can help them - Turgeon, Heather; Wright, Julie (TarcherPerigee book, an imprint of Penguin Random House, LLC, 2022)
"An intimate glimpse inside a silent epidemic that is harming teens and how parents can help them reclaim the restorative power of sleep. If you could protect your teen from unnecessary anxiety, depression, and chronic stress, and foster a greater sense of happiness and well-being in their life, wouldn't you? In Generation Sleepless, the authors of the classic guide to helping babies and young children develop healthy sleep habits The Happy Sleeper uncover one of the greatest threats to our teenagers' physical and mental health: sleep deprivation. Caught in a perfect storm of omnipresent screens, academic overload, night owl biology and early school start times, Generation Sleepless illustrates how our teens are operating in a constant state of sleep debt and social jet lag while struggling to meet the demands of adolescence."--